Dialogue at the Margin: Nicolás Gómez Dávila, Hernando Téllez, Mito Magazine, and Brief Argumentative Forms in Colombian Literature (2023)
This article focuses on the initial reception of Nicolás Gómez Dávila’s work, as presented by Hernando Téllez in Mito Magazine. It examines the emergence of brief argumentative forms in the Colombian magazine Mito and specifically explores the utilization of these forms by Hernando Téllez and Nicolás Gómez Dávila. First, the article discusses the relationship of both authors with forms such as the scholium, aphorism, diary entry, and essay. Subsequently, it examines the use of marginal forms in Mito Magazine by authors such as Alfonso Reyes, Jorge Gaitán Durán, and Rafael Gutiérrez Girardot. Finally, the appearance of argumentative texts by Téllez and Gómez Dávila in the magazine is analyzed to establish a dialogue between the two main proponents of brief argumentative forms in Colombian literature of the 1950s.